2023
DOI: 10.1021/jacs.3c04933
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Trapping of a Cyclic Diborylcarbene, an Electrophilic Carbene

Abstract: A carbene bearing two geminal boryl substituents, called diborylcarbene (DBC), has been predicted to be highly Lewis acidic in sharp contrast to the well-studied persistent carbenes stabilized by π-donating substituents. Studies on DBC have been limited to either the base-trapping or theoretical calculations. Herein, we developed chemical equivalents for DBC, namely, K/X-diborylcarbenoids 2 X (X = F or Cl). Treatment of 2 F with Al(C 6 F 5 ) 3 yielded [AlF(C 6 F 5 ) 3 ] − -stabilized DBC 1-FAl, which showed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 66 publications
0
2
0
1
Order By: Relevance
“…12) Nozaki und Kusumoto konnten experimentell die Vorhersage bestätigen, dass flankierende Boryl-Substituenten an einem Carbenzentrum zur Entstehung eines Lewis-sauren Diborycarbens führen. 13) Sie stellten Diborylcarbenoide her, die sich als Vorläufer für basenstabilisierte Diborylcarbene einsetzen lassen (Abbildung 11). Diese Veröffentlichung wirft Licht auf diese bisher wenig betrachtete Klasse von Carbenen und bewertet die Lewis-Azidität der Diborylcarbenspezies: Diese Substanzklasse gehört nun zu den stärksten neutralen Lewis-Säuren.…”
Section: Gruppe 2 -Erdalkalimetalleunclassified
“…12) Nozaki und Kusumoto konnten experimentell die Vorhersage bestätigen, dass flankierende Boryl-Substituenten an einem Carbenzentrum zur Entstehung eines Lewis-sauren Diborycarbens führen. 13) Sie stellten Diborylcarbenoide her, die sich als Vorläufer für basenstabilisierte Diborylcarbene einsetzen lassen (Abbildung 11). Diese Veröffentlichung wirft Licht auf diese bisher wenig betrachtete Klasse von Carbenen und bewertet die Lewis-Azidität der Diborylcarbenspezies: Diese Substanzklasse gehört nun zu den stärksten neutralen Lewis-Säuren.…”
Section: Gruppe 2 -Erdalkalimetalleunclassified
“…8 In principle, π-acceptors can be gainfully employed for this task, but this still often leaves the triplet as the ground state like in a recently reported diboryl carbene with a gap of more than 10 kcal mol −1 to the σ 0 π 2 singlet. 9 Hoffmann and Borden suggested that the experimentally known 2 H -imidazol-2-ylidene can be characterized as a σ 0 π 2 singlet ground state carbene while it was previously rather thought of as a carbodiimide (Fig. 1B).…”
mentioning
confidence: 99%
“…1C). Diborylcarbenes exemplify this conceptual approach; however, attempts to isolate these molecules have hitherto remained elusive ( 26 30 ). Other attempts to isolate σ 0 π 2 carbenes involve exploring postulated metallodiphosphinocarbenes with high electrophilicity ( 31 34 ).…”
mentioning
confidence: 99%